Research on the Implementation Path of Apprenticeship in Higher Vocational Colleges - Xie, Xiaoyan; BULGAA. A (International Journal of Social Sciences and Public Administration, 2025)
In the context of globalization and technological innovation, the traditional education system is unable to meet the demand for highly skilled personnel in industrial upgrading, and apprenticeship has become an important way to connect education and employment. Since 2014, China has promoted the development of apprenticeships through a number of policies aimed at deepening cooperation between colleges and enterprises, optimizing the curriculum system and improving the quality of talent training. However, the current implementation still faces problems such as low participation of enterprises, lagging curriculum development, poor college-enterprise cooperation, complex student management and imperfect incentive mechanism. Through theoretical analysis, this paper discusses the operation logic of apprenticeship system from the four mechanisms of interest driving, communication and coordination, training realization and quality assurance, and emphasizes the necessity of balance and coordination of interests of multiple subjects. In view of the implementation path, it puts forward strategies such as optimizing policy support (such as funding guarantee, protection of students' rights and interests), strengthening the functions of industry associations (policy coordination, standard formulation), and deepening college-enterprise cooperation (joint management, curriculum construction, teacher training). The research holds that the government-led, industry supervision, college-enterprise collaboration and the institutionalized construction of progressive training mode are the key to the construction of high-quality apprenticeship system with Chinese characteristics, which can provide stable talent support for industrial transformation.